Compressive behavior of hybrid double-skin tubular columns with ultra-high performance fiber-reinforced concrete (UHPFRC). (1st February 2019) - Wang, Weiqiang; Wu, Chengqing; Liu, Zhongxian
Highlights: Sudden stress reduction or stress fluctuations can be observed for the UHPFRC. Steel fiber addition significantly influence the compressive behavior of UHPFRC. UHPFRC in DSTCs can be more effectively confined than in FRP confined concrete. The suitability of existing model for the UHPFRC in DSTCs is investigated. Abstract: This study presents the results of an experimental program on the compressive behavior of hybrid fiber-reinforced polymer (FRP)-concrete-steel double-skin tubular columns (DSTCs) with ultra-high performance fiber-reinforced concrete (UHPFRC). In total 40 specimens, including 32 hybrid DSTCs and eight FRP confined solid concrete (FCSC) specimens, were prepared and tested under axial compression. In addition to hybrid UHPFRC DSTCs, hybrid DSTCs with ultra-high performance concrete without steel fiber addition (UHPC), high-strength concrete (HSC), and normal-strength concrete (NSC) were also tested. The investigated parameters included the FRP tube thickness, steel tube thickness, void ratio, steel fiber addition, concrete type, UHPFRC-filling inside the steel tube, and the column type. The test results indicate that the hybrid UHPFRC DSTCs can exhibit highly ductile behavior when a thick FRP tube is used. However, due to the ultra-high strength and the dense microstructure of UHPFRC, the hybrid UHPFRC DSTCs are likely to exhibit more brittle behavior than the hybrid DSTCs with NSC and HSC. Even though a high confinement level is provided, sudden stress reduction or stress fluctuations can be observed for the UHPFRC in hybrid DSTCs. The influences of FRP tube thickness, void ratio, steel fiber addition, and UHPFRC-filling inside the steel tube on the compressive behavior of the hybrid UHPFRC DSTCs are significant, while the influence of steel tube thickness is insignificant. Moreover, when compared to the FCSC specimens, the presence of an inner void is beneficial for the compressive behavior of UHPFRC in the hybrid DSTCs, especially when a thick FRP tube is used. Furthermore, the performance of existing stress-strain model to predict the compressive behavior of UHPFRC in the hybrid DSTCs is investigated.